Children’s Test Anxiety Scale: The French Adaptation of a Short Scale for youth - Binette-Laporte, Floriane; Plante, Isabelle; Chaffee, Kathryn; Fréchette-Simard, Catherine; Goulet, Mélissa; Dubeau, Annie; Journault, Audrey-Ann; Yale-Soulière, Gabrielle (Mesure et évaluation en éducation)

(untitled) (ADMEE-Canada, 2024)
Instruments used to measure test anxiety in school have generally been validated using English-speaking populations. Moreover, these instruments are often lengthy, making their administration in school settings more complex. Based on the Children’s Test Anxiety Scale (CTAS; 2004), this paper develops a French adaptation titled Questionnaire d’anxiété évaluative scolaire (QAES), followed by a short version, the Questionnaire d’anxiété évaluative scolaire-Courte (QAES-C). The psychometric properties of the QAES-C were examined in two complementary studies involving 1,212 and 387 Quebec students, respectively. Exploratory factor analysis (Study 1) and confirmatory factor analysis (Study 2) revealed a structure reflecting the three components of test anxiety (i.e., cognitive, physiological and behavioral). In both studies, these three subscales demonstrated high internal consistency. Overall, the findings suggest that the QAES-C has satisfactory psychometric properties, supporting its use for assessing test anxiety among French-speaking adolescents.